The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/bf02869207
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in heterogeneous TiO2 photocatalysis

Abstract: Current progress in the area of photocatalysis is presented, particularly regarding technological applications. Highly efficient TiO2 films on different substrates such as tile and glass have been developed for indoor environmental clean-up. TiO2 films coated on SiO2-precoated soda lime glass showed about 80% transparency and high photocatalytic activity towards the decomposition of thin oil films. A novel phenomenon, superhydrophilicity, has been observed on these transparent TiO2 coatings. In addition, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Semiconductor photocatalysis has been extensively studied for more than forty years for environmental purification [1] , [2] , [3] , anti-fogging/self-cleaning surfaces [4] , water splitting [5] and solar energy conversion [6] . It is expected that solar photocatalysts (semiconductor photocatalysis driven by the Sun) could help in solving the most emerging humanity problems, i.e., (1) energy, (2) water and (3) environment (three of “Top Ten Problems of Humanity” proposed by Prof. Smalley [7] ), where abundant and clean energy would enable the resolution of all other problems.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysis has been extensively studied for more than forty years for environmental purification [1] , [2] , [3] , anti-fogging/self-cleaning surfaces [4] , water splitting [5] and solar energy conversion [6] . It is expected that solar photocatalysts (semiconductor photocatalysis driven by the Sun) could help in solving the most emerging humanity problems, i.e., (1) energy, (2) water and (3) environment (three of “Top Ten Problems of Humanity” proposed by Prof. Smalley [7] ), where abundant and clean energy would enable the resolution of all other problems.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the NaOH washing could lead to the conversion of abundant surface-bonded Ti-F species into Ti-OH species, which would greatly improve the photocatalytic performance of the asprepared samples that washed with water only [24]. On the other hand, it is well known that the photocatalytic activity of TiO 2 -coated soda-lime glass was much lower than that of the TiO 2 -coated quartz due to the diffusion of Na + into the TiO 2 film from the soda-lime glass substrate during heat treatment [26,27]. However, there are very few reports focusing on the effect of Na + on the photovoltaic properties of TiO 2 materials in DSSCs.…”
Section: Introductionmentioning
confidence: 97%
“…[ 21 ] There are also reports confirming the lower photocatalytic activity of TiO 2 ‐coated soda–lime glass than that of the TiO 2 ‐coated quartz due to the diffusion of Sodium‐ion (Na + ) into the TiO 2 film from the soda–lime glass substrate. [ 22,23 ] However, there are only very few reports on the effect of Na + on the photovoltaic properties of TiO 2 materials in DSSCs. The photovoltaic properties of NaOH‐washed anatase TiO 2 nanosheets with exposed {001} facets were also investigated for DSSC.…”
Section: Introductionmentioning
confidence: 99%